IDENTIFIKASI MASALAH PROFESIONALISME CALON GURU PADA MAHASISWA PENDIDIKAN KIMIA FMIPA UNIVERSITAS NEGERI GORONTALO - Aminah, Siti; Baderan, K; Lukum, Astin; Isa, Ishak (Jurnal Entropi, 2009)
This research was aimed to know the problems of the teacher professionalism that faced of Chemistry Education students to Mathematic and Natural Science Faculty of Gorontalo State University after PPL, and to know the dominant problems about teachers professionalism.The result of this research showed that the teacher professionalism problems of student were (1) teacher base competence including managing teaching learning process and class, material mastery, using media and source of learning, so assessment., (2) doing KTSP including new and same item with old curriculum, different curriculum, KTSP component, applying CTL approach and its application to schools. The dominant problems about teacher professionalism that related to teacher base competence were using media and source of learning about 66,20%, so material mastery about 59%. The dominant problems related to doing CTL including application of CTL about 64% and KTSP application to schools about 63,50%.